The Influence of Service Quality, Price and Promotion on Consumer Satisfaction - Nur Aeni; Titania Agrelia (Kusuma Negara Business School, 2021)
Service quality is a comparison between the service perceived by consumers and the expected service quality for the level of excellence to meet consumer desires. Price is the value of a product in exchange for other products. Promotion is a specific strategy of personal advertising, sales promotion and public relations that a company uses to achieve its advertising and marketing objectives. consumer satisfaction is an assessment that the features of the product or service itself, provide a level of fulfillment related to pleasant consumption. The purpose of this study was to determine the effect of service quality, price and promotion on consumer satisfaction. The population in this study are consumers of the Wine Organizer, with 100 respondents obtained from the lemeshow formula. The data collection technique used in this study was by distributing it via google form. The data analysis method uses multiple linear regression with the help of the SPSS program. The results in this study explain that service quality affects consumer satisfaction, price affects consumer satisfaction, promotions affect consumer satisfaction.